THE NEW RULES OF ENGAGEMENT: CONSUMER DECISION-MAKING AND MOBILE MARKETING TRENDS - Ращенко, Анастасія (SWorldJournal, 2025)
The article explores how mobile devices reshape consumer behavior and challenge the traditional marketing funnel. Based on research from BCG, McKinsey, and others, it outlines the new, non-linear consumer journey shaped by streaming, scrolling, searching,